2022
DOI: 10.3390/jcm11113165
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes of Acute Graft Pyelonephritis with Bacteremia Due to Multidrug-Resistant Gram-Negative Bacilli among Kidney Transplant Recipients

Abstract: Acute graft pyelonephritis (AGP) is the leading cause of bloodstream infection in kidney transplant (KT) recipients. The prevalence of urinary tract infections caused by multidrug-resistant (MDR) Gram-negative bacilli is increasing. This 14-year prospective observational study sought to determine the clinical characteristics, risk factors, and outcomes of AGP with bacteremia due to MDR Gram-negative bacilli. Overall, 278 episodes of AGP with bacteremia due to MDR Gram-negative and non-MDR Gram-negative bacilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…However, we found that males were more likely to develop BSIU. This observation aligns with a similar finding reported by Sabe et al in their prospective observational study where male KTR were at higher risk of multidrug resistant graft pyelonephritis and bacteremia relative to female KTR 13 . These findings suggest that the anatomical differences contributing to greater bacteriuria risk in females may not translate to an increased risk of BSIU.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we found that males were more likely to develop BSIU. This observation aligns with a similar finding reported by Sabe et al in their prospective observational study where male KTR were at higher risk of multidrug resistant graft pyelonephritis and bacteremia relative to female KTR 13 . These findings suggest that the anatomical differences contributing to greater bacteriuria risk in females may not translate to an increased risk of BSIU.…”
Section: Discussionsupporting
confidence: 91%
“…This observation aligns with a similar finding reported by Sabe et al in their prospective observational study where male KTR were at higher risk of multidrug resistant graft pyelonephritis and bacteremia relative to female KTR. 13 These findings suggest that the anatomical differences contributing to greater bacteriuria risk in females may not translate to an increased risk of BSIU. To further understand why males may be at greater risk for BSIU, we performed a multivariable subgroup analysis of male KTR with bacteriuria that included urological history.…”
Section: Discussionmentioning
confidence: 92%
“…The impact of UTI on distant graft function is not fully understood. The predominance of pathogenic Gram-negative bacteria in urobiome of patients after kidney transplantation, indicated in some reports, highlights the problem of UTIs in recipients (Sabé et al, 2022) and a negative impact of early or late UTIs on the functioning of the transplanted kidney has been confirmed (Rani et al, 2017;Fiorentino et al, 2019;Pesce et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Bloodstream infection (BSI) has a high mortality and the number of BSI has been increasing for various risk factors, such as the widely application of central venous catheter (CVC). [1][2][3] According to the report from the China Antimicrobial Surveillance Network (CHINET), the number of specimens of BSI in China had increased from 296,052 in 2018 to 325,016 in 2021 (the report from the China National Drug Resistance Monitoring Network, https://www.carss.cn/sys/ Htmls/dist/index.html#/distribution?type=specimens). Our previous research also reported that the episodes of BSI had increased from 2010 to 2019 in the hospital where this study was conducted.…”
Section: Introductionmentioning
confidence: 99%